2021
DOI: 10.1002/ar.24625
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture, from the ancient to the current

Abstract: Acupuncture is characterized by the insertion of a fine metal needle through the skin of the human body at an acupuncture point (acupoint) in Traditional Chinese Medicine (TCM). It is an ancient form of therapy, and has a long history of prosperity and decline. Due to the persistent efforts of TCM practitioners, a number of well-designed clinical trials regarding acupuncture have been published in the past decade. Besides, numerous basic researches aiming to reveal the mechanisms of acupuncture have also been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 37 publications
0
46
0
3
Order By: Relevance
“…Nowadays, complementary and alternative medicine has been widely used in treating depression. Acupuncture is a Traditional Chinese Medicine therapy, which inserts a fine metal needle through the skin at an acupoint (Zhu et al, 2021). Acupuncture has become a well-recognized alternative therapy for treating depression in the clinical practice and has been shown to alleviate the symptoms of depression (Qu et al, 2013;Zhao et al, 2019).…”
mentioning
confidence: 99%
“…Nowadays, complementary and alternative medicine has been widely used in treating depression. Acupuncture is a Traditional Chinese Medicine therapy, which inserts a fine metal needle through the skin at an acupoint (Zhu et al, 2021). Acupuncture has become a well-recognized alternative therapy for treating depression in the clinical practice and has been shown to alleviate the symptoms of depression (Qu et al, 2013;Zhao et al, 2019).…”
mentioning
confidence: 99%
“…TCM emphasizes the importance of protecting the brain and the regulation of the Qi flow in the body (Zhu et al, 2021). The pathological process in AD can disturb the balance of Yin and Yang and may contribute to dementia.…”
Section: Acupuncture Restores the Bloodbrain Barriermentioning
confidence: 99%
“…Acupuncture has been recognized as a crucial therapy in traditional Chinese medicine (TCM), and is also accepted as a complementary and alternative therapy in the world. Acupuncture therapy could be traced back to the Neolithic period of China and has spread to the whole world for over 1,000 years (Zhu et al, 2021). Acupuncture involves insertion of a sterile stainless-steel needle into the acupoint to stimulate the meridian activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture, a therapy created by the ancient Chinese, is characterized by the insertion of a fine metal needle through the skin of the human body at an acupuncture point. Zhu, Li, Yang, and Liu (2021) reported that acupuncture was effective in improving the sleep quality and psychological health in primary insomnia patients than sham acupuncture.…”
Section: Introductionmentioning
confidence: 99%